Framing Analysis of the Reporting Scenario of Gibran Becoming Vice President on CNN Indonesia Media - Kurnia, Moh. Mirza; Sjuchro, Dian Wardiana; Wirakusumah, Teddy Kurnia (International Journal of Science and Society, 2024)
Insert the current political reality in Indonesia has become a complex and diverse focal point of attention. In the context of the 2024 presidential election (Pilpres 2024), the Constitutional Court's decision regarding the minimum age requirement for vice presidential candidates has sparked widespread controversy. This issue has become a subject of debate because age limits are considered one of the criteria for political leadership qualifications. Framing Analysis is utilized to understand how the media, including CNN Indonesia, present Gibran and the issues surrounding his candidacy as vice president. This research employs a qualitative approach and constructivism paradigm to elucidate this phenomenon. By leveraging Robert N. Entman's Framing Analysis model, this study aims to gain a deeper understanding of how the media influences public perception of Gibran and the political issues associated with him. The data used consists of news reports from CNN Indonesia, specifically textual coverage from October 2023, which is deemed influential in shaping public opinion and perception regarding the 2024 presidential election. Through this research, it is hoped that the understanding of how the media comprehend and interpret specific political realities, as well as their impact on public opinion and the democratic process, will be revealed.